(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
Thin films are developed for multi-purposes, such as optical waveguides, corrosion resistant coating, car tinting, and glass coatings. Each thin film is created and designed with a specific purpose and function. The purpose of this research was to fabrication anti-reflective films on glass Indium Tin Oxide (ITO) usually used as an electrode in Dye-sensitized Solar Cell (DSSC). In this research, the material used involved solution 100.12 g/mol Methyl Methacrylate (MMA) and 3% Polystyrene(PS) with a spin coating method. In this study, polystyrene and methyl methacrylate solution dripped on ITO glass was then rotated at 1000, 1500, 2000 and 2500 rpm. This study shows that polystyrene and methyl methacrylate materials can be used as an anti-reflection coating on the ITO substrate by a spin coating method. The methyl methacrylate material is good for anti-reflection coating at 400-475 nm wavelength region, while the polystyrene material is good for 475-700 nm wavelength. The addition of a 3% polystyrene coating on ITO glass can increase light transmission at a wavelength of 475-700 nm by 1.14% when compared to ITO glass without a polystyrene coating. The highest light transmission of 90.11% occurs at a wavelength of 420 nm when the ITO glass is coated with methyl methacrylate.